2007
DOI: 10.1620/tjem.211.23
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nitrosative and Oxidative Stress in Platelets of Migraine Patients

Abstract: The molecular mechanisms of migraine have not been fully clarified yet. Increased nitrosative and oxidative stress may be associated with migraine attacks. Platelets may play an important role in migraine patients and they can reflect the lability of tissues to nitrosative/oxidative stress. In the present study, we aimed to determine the levels of nitrosative and oxidative stress markers in platelets of migraine patients during headache-free and attack periods. A total of 56 subjects (22 migraine without aura,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 43 publications
5
64
0
Order By: Relevance
“…It is rapidly oxidized by tissue oxygen to the stable end products, nitrate and nitrite. Thereby, to best index of overall NO production in the circulation, is the total concentrations of both nitrate and nitrite [5,6]. NO is one of the substances that takes a part in the pathophysiology of migraine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is rapidly oxidized by tissue oxygen to the stable end products, nitrate and nitrite. Thereby, to best index of overall NO production in the circulation, is the total concentrations of both nitrate and nitrite [5,6]. NO is one of the substances that takes a part in the pathophysiology of migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced endothelial NO and superoxide anion release may cause migraine through cerebral blood flow changes. In some studies, oxidative stress due to increased NO has been found especially during attacks in patients with migraine [4,5]. It is emphasized that neurogenic inflammation, endothelial dysfunction and oxidative stress have a role in migraine pathogenesis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing evidence of oxidative stress and vascular endothelial activation in migraine (23)(24)(25)(26)(27), the abovementioned biomarkers of endothelial dysfunction have not been comprehensively analyzed in relation to WMLs. Therefore, our objective in the present study was to quantify the L-arginine, ADMA and SDMA serum concentrations of migraine patients F o r P e e r R e v i e w 4 with or without cerebral WMLs in a headache-free period, to detect group differences between lesional and non-lesional migraineurs, to investigate the effect of migraine characteristics, and to determine the differences between migraine patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of SOD, a radical-scavenging enzyme, is lower in migraine patients than in healthy controls; this suggests enhanced vulnerability to oxidative stress during migraine [4] . Interestingly, nitric oxide (NO) metabolites and lipid peroxidation are increased during a migraine attack in platelets, in contrast to headache-free periods [5] . Moreover, in chronic migraine patients, NO serum levels and SOD activity are decreased and serum peroxide levels are increased, in contrast to healthy controls [6] .…”
Section: Introductionmentioning
confidence: 99%